AB0981 Hand Joint Inflammation in Early Ra: Clinical Ultrasound and Fluorescence Optical Imaging Diagnostics. (15th July 2016) - Kisten, Y.; af Klint, E.; Györi, N.; Karlsson, A.; Levitsky, A.; Rezaei, H.; Arnaud, L.; van Vollenhoven, R.
Abstract : Background: Altered microcirculation (abnormal perfusion/capillary leakage) of synovial tissue can be detected early using Fluorescence Optical Imaging (FOI). FOI utilizes an intravenous fluorophore 1, 2 that displays high-resolution hand images that can be analyzed visually (FOI-v) in real-time, or by using digital Disease ACTivity (DACT) scoring methods. We previously reported FOI's sensitivity and specificity in detecting silent synovitis in various rheumatic diseases 1 . Objectives: Here, we test the diagnostic performance of FOI-DACT in detecting subtle hand joint inflammation in early rheumatoid arthritis (eRA), as compared to clinical evaluation and MusculoSkeletal UltraSound (MSUS). Methods: Fingers and wrists of patients with eRA were assessed by clinical examination, MSUS and FOI-DACT imaging. Inflammation was defined as having synovial hypertrophy/effusions and intra-articular Doppler signaling on MSUS, and as increased optical intensities on FOI-v. Scores of DACT≥1 were considered indicative of disease activity. Results: 1326 joints of 39 eRA patients [72% females, 56% previous/current smokers, 54% RF(+) and 69% ACPA(+)] were studied. The incidence and mean number ±SD of joints inflamed by clinical, MSUS and FOI-v were 23% (7.8±8.1), 29% (9.7±7.7) and 30% (10.3±7.2), respectively. Using MSUS as a reference, FOI-DACT was 95% (35/37) accurate in identifying patients with active disease, 24% (9/37) of whom had erosive RA. High correlations and agreements emerged between MSUS and FOI-v (r=0.803, p<0.001; kappa±SE:0.70±0.02 [95% CI 0.67–0.75]), clinical and FOI-v (r=0.732, p<0.001; kappa±SE:0.56±0.03 [95% CI 0.51–0.61]) and MSUS and clinical (r=0.793, p<0.001; kappa±SE:0.59±0.03 [95% CI 0.54–0.64]). The sensitivity, specificity, NPV and PPV of inflammation by FOI-v was 81% (308/380), 90% (854/946), 61%, and 96% respectively. Of the clinically negative but MSUS positive (145/1023) joints, 68% (Subclinical: 98/145) were also FOI positive. Remarkably, one patient had 15 joints that were FOI-DACT positive and MSUS negative, but a month later, the same joints became MSUS positive. Although the wrists and MCPs were frequently inflamed, DIP joint inflammation was noted in 12 patients by FOI-DACT and MSUS. Nine of these patients had osteoarthritis by conventional radiography. Conclusions: In early RA, Fluorescence Optical Imaging (FOI) coupled with digital Disease ACTivity (DACT) scoring correlates well with MSUS, and has a high positive predictive value. FOI-DACT emerges as a useful automated quantitative scoring method for synovial inflammation, and may be used in monitoring the effects of therapy. References: Kisten Y, Györi N, af Klint E, et al. 2015 Detection of clinically manifest and silent synovitis in the hands and wrists by fluorescence optical imaging. RMD Open 2015;1: e000106. doi: 10.1136/rmdopen-2015-000106 (http://rmdopen.bmj.com/content/1/1/e000106.full.pdf+html ) Glimm AM, Werner SG, et al. Analysis of distribution and severity of inflammation in patients with osteoarthitis compared to rheumatoid arthritis by ICG-enhanced fluorescence optical imaging and musculoskeletal ultrasound: a pilot study. Annals of the Rheumatic Diseases. Published online Aug. 26, 2015. (http://dx.doi.org/10.1136/annrheumdis-2015-207345 ). Disclosure of Interest: None declared